Gorontalo Local Government's Response To Legal Vacuum On Electric Bikes - Fitriana Nur Biya (Universitas Negeri Gorontalo, 2019)
The purpose of this study is to find out the attitude of Gorontalo local governments to address the legal vacuum towards electric bicycles. The methods used in this study are normative research and The types of approaches used are the legal approach, the conceptual approach, and the case approach. The technique of analyzing legal materials in this study uses systematic interpretation methods. The results showed that the Gorontalo regional government in addressing the legal vacuum regarding the regulation of electric bicycles in the Gorontalo area is first to take precedence over what is the main problem, then trace whether the transportation has reached 50% of users for the entire Gorontalo area. This needs to be known so that it can be regulated by the local government without limiting the space of the community. Thus, holding regional rules related to the regulation of electric bicycles is still an obstacle from the point of view of the provincial DPRD why the use of such vehicles is considered to have not reached an effective amount causing the need for regional rules to regulate the use of such vehicles. With the advancement of transportation in a region, the local government should have taken steps first before it becomes a result of an event that is not organized by the local government. With this problem, the government cannot suppress the public and carry out doctrinal laws related to the rules of the use of electric bicycles, so that the theory of repressive laws cannot be implemented. The law should be able to regulate society to be able to comply with existing rules, but the rules can not be implemented. Keywords: Attitude; Responding; Electric Bicycle